RIVERBAN MANAGEMENT BECOME A CREATIVE PUBLIC SPACE FOR MILINEAL CONTENT CREATORS - Eka Martyna Theodora; Junaerdi Nababan; Nidya Banuary; Sungguh Ponten Pranata; Hana Salsabila Lubis (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
This community service project aims to transform the banks of the Deli River in Kelurahan Kota Bangun, Medan Deli, into creative public spaces for millennial content creators. The initiative addresses environmental degradation and limited public spaces, which hinder economic and creative growth. The project involves reforestation, with a target of achieving 30% green coverage along the riverbanks, and the establishment of open public spaces to stimulate creative activities. By fostering local youth engagement and leveraging digital media, the project seeks to enhance community well-being, promote environmental awareness, and empower millennials to create marketable content. The expected outcomes include increased creativity, economic improvement, and environmental sustainability, supported by ongoing community and academic collaboration.